Transformasi Digital Pendidikan Islam: Pemanfaatan Laravel dalam Pengembangan Sistem Informasi Akademik di TPA Mesjid Al-Jama’ah Padang - Asri, Ervan; Yance Sonatha; Putri, Dinda Meivianti Dwi (SOTVI - Society of Visual Informatics, 2024)
Managing academic information in educational institutions often faces challenges that require high efficiency. Manual processes in collecting and managing academic data can lead to complexity and errors. Taman Pendidikan Al-Qur’an (TPA) Mesjid Al-Jama’ah in Padang experiences similar issues, particularly in managing registration, attendance, grades, and tuition payments. This research aims to develop an Academic Information System based on Laravel for TPA Mesjid Al-Jama’ah, encompassing four user levels: admin, prospective students, students, and teachers. The Rapid Application Development (RAD) methodology is used in system development, involving stages such as requirements determination, prototyping, development and feedback collection, and product implementation and finalization. The system is built using UML, PHP, Laravel, and MySQL to ensure data is well-organized and free from redundancy. The implementation results indicate that this system facilitates online registration and data management, and helps teachers input grades and attendance efficiently. It is recommended that the system be further developed to include TPA financial management and add features for printing summaries and exporting data to Excel, to enhance the efficiency and effectiveness of information management at TPA Mesjid Al-Jama’ah.